If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+1/5(b)=6
We move all terms to the left:
5+1/5(b)-(6)=0
Domain of the equation: 5b!=0We add all the numbers together, and all the variables
b!=0/5
b!=0
b∈R
1/5b-1=0
We multiply all the terms by the denominator
-1*5b+1=0
Wy multiply elements
-5b+1=0
We move all terms containing b to the left, all other terms to the right
-5b=-1
b=-1/-5
b=1/5
| (2u+7)(3u-1=0 | | (5x-7)(-x+9)=0 | | f=4/22 | | s^2+10s+13=0 | | x+.50=2x+.20 | | 3×-4y=12 | | 4*1.2-1.2x+3.4x=8.1 | | W^2+10w=880 | | X^+25=10x | | -3(2x+7)+(-4x)=-8 | | 40/7x+15/7x=25/14 | | -2(9x)=36 | | -3/11/3=-1/2x | | 3(2x+7)=2x+16 | | -14x+14=-13x-6 | | 40/7x+15/7x=111/14 | | -31/3=-1/2x | | x+2+2x+x=3x-1+4x+3x | | 8x+84=11x | | 4x-3x=6x3 | | 68(a+59)=42 | | -3(2x+7)+(-4)=-8 | | 68a+59=42 | | x+9x+20=90 | | x+9x20=90 | | -48-(-46)=x/10 | | 4(x+59=35 | | 8x+2+4x-6=4 | | -x^-3x-2=0 | | 16x-8=9x | | 7x+3=9x−13x= | | 4x-2+x²=6+x² |